Morfometrik dan Komposisi Spesies Penyusun Ikan Nike di Perairan Marisa Kecamatan Marisa Kabupaten Pohuwato - Thaib, Nur Afni; Sahami, Femy Mahmud; Salam, Aziz (The NIKe Journal, 2024)
This study aims to know the morphometrics and species composition of the shoal of Nike fish in Marisa Waters, Marisa Sub-districh, Pohuwato Regency. This study was conducted from Desember 2022 to March 2023. The samples obtained are all types of Nike fish caught by fishermen in Marisa Waters, as much as 220 ml. All samples are observed and grouped based on the melanophore pattern and then carried out the morphometric measurements using the Image-J application. The finding shows that Nike fish in Marisa Waters morphometrically has one distinguishing characteristic: PL (Preorbital Length). The result of analysis of the composition of Nike fish during the study period, from the highest to the lowest, are: S. longifilis (98.25%), B. segura (1.05%), S. parvei (0.38%), S. semoni (0.17%), B. belobranchus (0.10%), and S. cynocephalus (0.06%).